Level of knowledge on risk factors and preventive measures for breast cancer in health science students - Delgado-Díaz, Noelia (2020)
Introduction: breast cancer is one of the most common cancers worldwide and in Peru. Health studentsneed to know preventive measures and risk factors. Objective: to assess the level of knowledge aboutrisk factors and prevention measures for breast cancer in students of the private medical school, 2019.Methods: a quantitative, descriptive cross-sectional study was conducted with a sample of 319 studentsfrom the Faculty of Medicine of the Universidad Católica Santo Toribio de Mogrovejo in 2019, who havebeen enrolled in one of the professional schools. We used a questionnaire consisting of 18 questions, 5items that addressed sociodemographic data, and 13 measured the level of knowledge about risk factorsand preventive measures of breast cancer. Descriptive statistics were used. Results: After exclusion,there were 292 students, 72% were women. The mean age was 20.5, 23.6% were from the second year.The least known risk factors were drinking alcohol, being over 45 years of age, menarche before 12years of age, and menopause after 55 years of age, and the least known prevention measures were:correct age for mammography 71% and frequency for self-examination 63% in a higher percentage.Conclusion: knowledge about risk factors and breast cancer prevention measures was adequate.